The Impact of Pepper Production on Malaysian Economic and the Need for Nutraceutical Diversification - Olalere, Olusegun Abayomi; Nour, A. H.; Alara, Oluwaseun Ruth; Mani Malam, Ahmad (Universiti Malaysia Pahang, 2016)
Pepper is an important agricultural crop with nutritional, economical and medicinal benefits. Malaysian being the fifth largest producer of pepper has experience a decline in the price and economic value of the product. Owning this decline needs then arise for the diversification of pepper products into other by-products in order to increasing the economic potential of Malaysia. This necessitated research into the extraction of bioactive compounds embedded in pepper and help on harnessing the medicinal and economic value of this essential commodity. This review elucidated the historical evolution of pepper production in Malaysia,the regulation of its marketing and its potential for medicinal diversification.